2000
DOI: 10.1348/026151000165562
|View full text |Cite
|
Sign up to set email alerts
|

Shame and guilt in children: Differential situational antecedents and experiential correlates

Abstract: Situational antecedents and experiential correlates of shame and guilt in children were examined by having 6-11-year-olds give ratings of the extent to which two types of situations would elicit a protagonist's feelings of shame and guilt. It was predicted that one type of situation should elicit both shame and guilt, because the protagonist caused harm to another person by behaving incoherently or incompetently. The other type of situation was predicted to elicit more shame than guilt, because the protagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 19 publications
7
61
2
1
Order By: Relevance
“…Our results also support the notion that guilt promotes the desire to amend or repair situations in which a moral norm or rule has been violated (e.g., Kochanska et al, 1995;Malti & Latzko, 2012;Olthof et al, 2000) and extend existing empirical evidence linking guilt and reparation in early childhood (Kochanska et al, 1995) to include middle childhood. Thus, reparation may stem from both other-oriented feelings of sympathy and selffocused feelings of guilt following transgression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results also support the notion that guilt promotes the desire to amend or repair situations in which a moral norm or rule has been violated (e.g., Kochanska et al, 1995;Malti & Latzko, 2012;Olthof et al, 2000) and extend existing empirical evidence linking guilt and reparation in early childhood (Kochanska et al, 1995) to include middle childhood. Thus, reparation may stem from both other-oriented feelings of sympathy and selffocused feelings of guilt following transgression.…”
Section: Discussionsupporting
confidence: 86%
“…However, only one study, conducted with a sample of 2-year-old children, has provided empirical support for a positive relation between sympathy and reparative behavior (Zahn-Waxler et al, 1992). Likewise, despite substantial theorizing linking guilt to increased reparative behavior (e.g., Ferguson, Stegge, Miller, & Olsen, 1999;Olthof, Schouten, Kuiper, Stegge, & Jennekens-Schinkel, 2000), empirical support for this relation is limited to a single study from early childhood (e.g., Kochanska et al, 1995).…”
Section: Moral Emotions and Reparative Behaviormentioning
confidence: 99%
“…Another theoretical issue concerning guilt specificity, to which the present study contributes for the first time from a neuroscientific perspective, pertains to a current debate within psychology and philosophy as to what uniquely distinguishes the 2 emotions guilt and shame from each other (Tangney et al 1996;Olthof et al 2000;Teroni and Deonna 2008). Because a key aspect of this debate focuses on the notion of a differential involvement of self-versus other-referential processing in guilt and shame, we tested whether emotional circuits recruited by guilt versus shame showed distinct patterns of overlap with selfor other-related representations in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these emotions are not only thought to represent prototypes of the ''moral'' or ''self-conscious'' emotions (Leary 2007;Tangney et al 2007) but also appear phenomenologically and functionally very similar. Moreover, guilt and shame typically tend to co-occur in many situations (Eisenberg 2000;Olthof et al 2000). However, a critical distinction has been proposed between these 2 emotions with respect to the role of selfrelated representations (Tangney et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although shame has received increased attention in violence research, less is known about how bullying victimization relates to shame. To date, the bullying literature has mainly focused on the shame experienced by the bully or bystander, not shame experienced by the target of bullying (Ahmed & Braithwaite, 2004; Mazzone, Camodeca, & Salmivalli, 2016; Olthof, 2012; Olthof, Schouten, Kuiper, Stegge, & Jennekens-Schinkel, 2000). A recent study found that the victim’s shame mediated the association between experiencing peer victimization and a range of psychological distress in adolescents, suggesting that shame may be a mechanism by which peer victimization may influence mental health (Irwin, Li, Craig, & Hollenstein, 2016).…”
Section: Introductionmentioning
confidence: 99%